Reconstruction of the seals of the khans of the Inner Horde (Bukey Horde): identification of symbols and attributes of seals - Kartaeva, Тәттiгүл; Daubaev, Естай; Altynbekova, Элина (Turkic Studies Journal, 2023)
The seals used by the authorities in the history of Kazakhstan before the twentieth century can be grouped and systematized as follows: seals with archeographic symbols; seals with patterns, pictorial signs; seals with a portrait image; coat of arms seals; seals with stamps without the name of the owner; stamps with the name of the owner; relief seals without the name of the owner; relief seals with the name of the owner. Although Kazakh khans and sultans stamped their seals in the form of rings, they did not wear them on their hands every day, and when certifying documents, the pedestal was worn on the finger in the «aynateris» way, i.e. with a pointed head up (a bird’s nose is negative when wearing a «kusmuryn» ring) or certified with holding the pedestal in the hand. But judges, rich people, volost governors, tarkhans, batyrs and elders had round, convex, square or stone seals. The shape, that is the image of the ring seal of the Khans and sultans, corresponded to the image of the top of the military banners. The pommel of the banner and the seal are the attribute of power. The fact that the head part of both attributes of power is directed upwards proves that they were generally recognized in the traditional environment. The originals (originals) of the seals of the Kazakh Khans and sultans have not been preserved under the influence of colonization. The authors share their experience in reconstructing the seal and revealing the mystery of the symbols on the front of the seal.